Огляд методів дослідження та оптимізації машинних технологій утилізації відходів тваринництва - Скляр, Олександр Григорович; Скляр, Радміла Вікторівна; Комар, Артем Станіславович; Sklіar, Oleksandr; Skliar, Radmila; Komar, Artem (Запоріжжя : 2023, 2023)
UA: В статті наведено огляд методів дослідження та оптимізації машинних технологій утилізації відходів тваринництва, а саме гною та посліду. Розглянуті переваги прийняття оптимальних рішень із використанням ПЕОМ, статистичні моделі у вигляді одновимірних та багатовимірних рівнянь регресії та динамічні системи, методи лінійного та нелінійного програмування у дослідженнях з механізації процесів сільськогосподарського виробництва. Однією з основних задач під час проведення досліджень із механізації процесів сільськогосподарського виробництва є отримання достовірних статистичних моделей, їх дослідження та оптимізація стосовно конкретних критеріїв або умов виробництва. Особливу увагу приділено використанню методу Парето-оптимізації для порівняльної оцінки технологічних процесів видалення, переробки та використання підстилкового гною в біологічно активні добрива. EN: The article provides an overview of the methods of research and optimization of machine technologies for the disposal of livestock waste, namely manure and droppings. The advantages of optimal decision-making using personal computers, statistical models in the form of unidimensional and multidimensional regression equations and dynamic systems, linear and non-linear programming methods in research on the mechanization of agricultural production processes are considered. One of the main tasks during research on the mechanization of agricultural production processes is obtaining reliable statistical models (solving the problem of identification), their research and optimization in relation to specific criteria or conditions of production. It is shown that the model of the multi- level process of technological design with stepwise selection of solutions at each level is characterized by high efficiency, because the user at each stage of design has the opportunity to select several options closest to the best option. Special attention is paid to the use of the Pareto-optimization method for comparative evaluation of technological processes of removal, processing and use of litter manure into biologically active fertilizers. The peculiarity of multi-criteria Pareto optimization consists in the effective preliminary assessment of options with different criteria values, as a result of such a comparison, technologies are ranked by degree of efficiency. The analysis of the totality of technological processes of manure (excrement) utilization and relationships with influential factors determines significant a priori uncertainty of conditions. The variety of goals and means of solving tasks determine the need to involve additional information of an interdisciplinary nature, especially the theory of the course of biochemical processes. In this regard, there is currently a tendency to intellectualize the processes of forecasting the state of the object being studied or the phenomenon based on the implementation of theoretical provisions, practical developments in informatics and artificial intelligence in the space of solving the tasks.
Overview of methods of research and optimization of machine technologies of animal waste disposal
Скляр О. Г., Скляр Р. В., Комар А. С. Огляд методів дослідження та оптимізації машинних технологій утилізації відходів тваринництва. Науковий вісник Таврійського державного агротехнологічного університету : електронне наукове фахове видання. Запоріжжя : ТДАТУ. 2023. Вип. 13, том 2. C. 97-108.
Keywords: методи дослідження; оптимізація; утилізація; гній; послід; математичні моделі; технологія; технологічний процес; research methods; optimization; utilization; manure; litter; mathematical models; technology; technological process